2020
DOI: 10.18585/inabj.v12i4.1293
|View full text |Cite
|
Sign up to set email alerts
|

Co-treatment of Brazilein Enhances Cytotoxicity of Doxorubicin on WiDr Colorectal Cancer Cells Through Cell Cycle Arrest

Abstract: BACKGROUND: The presence of adverse side effects limits the use of doxorubicin (Dox) despite its cost-effectiveness compared to other chemotherapeutic agents. Brazilein (Be), the major compound of Caesalpinia sappan, performs co-chemotherapeutic potency in several cancer cell lines. This study evaluates the chemosensitizing effects of Be to Dox on colon cancer cell line, WiDr.METHODS: The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay was conducted to evaluate the cytotoxic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Brazilin was also reported to enhance the cytotoxic effect of chemotherapeutic agent. Combining brazilin with Adriamycin or cisplatin potentiates the inhibition of MCF7/Her-2 cells migration and the growth inhibition of WiDr cell lines (Utami et al, 2020).…”
Section: Research Articlementioning
confidence: 99%
“…Brazilin was also reported to enhance the cytotoxic effect of chemotherapeutic agent. Combining brazilin with Adriamycin or cisplatin potentiates the inhibition of MCF7/Her-2 cells migration and the growth inhibition of WiDr cell lines (Utami et al, 2020).…”
Section: Research Articlementioning
confidence: 99%
“…The accurate evaluation of subtle or minute normal pressures plays a vital role in precisely gauging external stimuli exerted on curved and energetic surfaces, such as human epidermis and organic tissues [123]. Due to their porous structures and remarkable elasticity, electrospun nanofiber rugs exhibit exceptional resilience when subjected to repeated external pressure.…”
Section: Applications Of Electrospun Nanofibersmentioning
confidence: 99%
“…The viability of combined sample added at different time points resulted in more cell death as compared to administration of doxorubicin or the extract alone. It has been observed that doxorubicin-induced WiDR cell cycle arrest in the S and G2/M phase (Utami et al 2020). Considering the higher level of cell death due to different time points of administration of extract towards doxorubicin suggested that doxorubicin may induced cell cycle arrest which then be abrogated by the presence of extract.…”
Section: Cytotoxic Activitiesmentioning
confidence: 99%